BRACHIAL BICEPS RUPTURE RECOVERY IN ATHLETES - Jacek Sobon; Girigan Vlăduţ Dumitru; Benedek Florian (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
After a brachial biceps rupture, the affected limb will be unavailable until the recovery, handicap that have a big influence not only to the evolution as a individual but also the maintaining of an optimum level of life. The recovery of the muscle ruptures is quite complex and implies a lot of stages. It begins with the immobilization of the segment immediately after the accident happens. Continuos with the removal of the pain that apears inevitably and the fight with the inflammation. After that, by various kinetic techniques we fallow the muscle modeling, keeping the joint mobility, the muscle toning and the propioceptive reeducation.